The Role and Duty of Traditional Leadership in Strengthening the Insecure Land Rights of Rural Communities in South Africa - Poswa, Xavia (Journal of Law, Society and Development, 2025)
This paper delves into the persistent challenges of insecure and weak land rights among rural landholding communities in South Africa, despite constitutional protections and legislative efforts. Section 25(6) of the Constitution mandates the provision of legally secure tenure or comparable redress for communities and individuals affected by historically discriminatory land practices. Over the last 25 years, Parliament has enacted several laws aimed at rectifying the issue of insecurity of land tenure. However, these legal measures have repeatedly fallen short of addressing the issue of informal land rights of rural communities. What has bedevilled these laws, among other things, is their failure to reflect the voices of rural communities on how best to secure and strengthen their land rights in a manner that gives effect to the “living customary law” they observe and follow. Instead, the enacted laws have often mirrored the interests of traditional leaders who, under the misconception of ownership, exert control over land and its allocation within their jurisdictions. This paper adopts a desktop approach to examining the legislative efforts undertaken to strengthen the security of land tenure and the possible reasons why these efforts have been fruitless so far. By focusing on the lived experiences of some of these communities and the operational dynamics of living customary law, the research highlights that the voices of rural communities (as evidenced by real life examples, which will be unpacked in detail), guided by living customary law, are indispensable to addressing this issue. The findings suggest a need for the government, traditional leaders and Parliament to listen to rural voices.